2011
DOI: 10.1080/10401334.2011.611771
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Publication Rates of Clerkship Directors in Internal Medicine (CDIM) Annual Meeting Abstracts 1995–2005

Abstract: These findings may serve as an indicator of the quality of the educational meeting. It may further stimulate efforts to develop programs to help program attendees achieve scholarly publications for work presented and serve as a benchmark against which future meetings may be judged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Rates of peer-reviewed publication for medical education abstracts in this study were similar to previously reported rates for traditional biomedical research, 2 and were higher than rates reported for medical education scholarship presented at the Association of American Medical College's Research in Medical Education (RIME) conference (37 %), 4 the Canadian Conference on Medical Education (CCME, 32 %), 4 the Clerkship Directors in Internal Medicine (CDIM) national meeting (35 %), 3 and the Council on Medical Student Education in Pediatrics (COMSEP) annual meeting (34 %) 5 . There may be several reasons for these differences in publication rates.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Rates of peer-reviewed publication for medical education abstracts in this study were similar to previously reported rates for traditional biomedical research, 2 and were higher than rates reported for medical education scholarship presented at the Association of American Medical College's Research in Medical Education (RIME) conference (37 %), 4 the Canadian Conference on Medical Education (CCME, 32 %), 4 the Clerkship Directors in Internal Medicine (CDIM) national meeting (35 %), 3 and the Council on Medical Student Education in Pediatrics (COMSEP) annual meeting (34 %) 5 . There may be several reasons for these differences in publication rates.…”
Section: Discussionsupporting
confidence: 84%
“…[3][4][5] The report on COMSEP abstracts spanned many years, showing a growing percentage of publication over time, which would MERSQI Medical Education Research Study Quality Instrument, UME undergraduate medical education, GME graduate medical education, CME continuing medical education, IME innovations in medical education affect the overall average publication rate. 5 The report on the CDIM abstracts also spanned many years (1995-2005), although the results did not demonstrate a significant increase in publication rates after 2002.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations